Informe de Evaluación y Análisis De Técnicas Quirúrgicas Para Prolapso Vaginal Bovino y Bienestar Animal - Cuevas Tibaduiza, Yelixa (Universidad Antonio Nariño, 2024)
The following report describes the activities carried out during the internship, which began on August 12, 2022, and ended on December 2 of the same year, at the Namigni animal sanctuary, located in La Calera, Cundinamarca. Multiple functions are performed at this site, such as: general clinical examination, reproductive checkups, medication calculation and administration, surgical assistance for cattle, horses, and other species, implementation of strategies for the improvement of pastures and rangelands, birth care, medical consultations, sample collection and submission, and the study of the toxic potential of local fauna. Animal welfare practices are also promoted to ensure optimal living conditions for the animals.